Herpes simplex virus-1, epstein-barr virus, and human cytomegalovirus in the saliva of periodontally diseased pregnant and nonpregnant women: A cross-sectional analytical study - Paramjit Kaur Khinda; Dinesh Rao; Surender Pal Singh Sodhi; Anita Mehta; Sanjeev Kumar Salaria (Wolters Kluwer Medknow Publications, 2023)
Context: Periodontal disease is commonly found among pregnant women. Viruses may play a key role in the etiology of periodontal disease through a variety of mechanisms that work alone or in tandem. Many researchers have explored the possible role of herpes viruses in periodontal disease, but extremely limited studies have evaluated the effect of pregnancy on herpes viruses in women with periodontal disease. Aims and Objectives: To study the effect of pregnancy on herpes simplex virus-1, Epstein-Barr virus (EBV), and human cytomegalovirus in women with periodontal disease and to evaluate the presence of herpes viruses within the saliva of pregnant and nonpregnant women with periodontal disease. Settings and Design: The study design involves a cross-sectional analytical study. Materials and Methods: The study consisted of 50 females aged between 18 and 35 years. Group I comprised pregnant women at any gestational age with periodontal disease and Group II comprised nonpregnant women with periodontal disease. The clinical parameters assessed were plaque index, gingival index, bleeding on probing, probing pocket depth, and clinical attachment loss. Nonstimulated whole saliva was utilized for the detection of three herpes viruses by multiplex polymerase chain reaction. Statistical Analysis Used: The categorical variables and research parameters were compared using the Chi-squared test and the Student's t-test. Results: Both groups tested positive for the three herpes viruses, but only a significant increase was observed in EBV in Group I participants on the intergroup comparison. Conclusions: The presence of EBV in the saliva of women with periodontal disease was found to be more likely during pregnancy.